Pemanfaatan Penggunaan Sosial Media Dengan Bijak Dalam Teknologi Informasi Di Era Digital Di SMK Media Informatika - Chairul Anwar; Ardijan Handijono; Abdurrahman Harits (PT Jurnal Cendekia Indonesia, 2025)
The purpose of this Community Service activity is to improve digital literacy and awareness of social media ethics of students at SMK Media Informatika, South Jakarta City. Students are an age group that is very active in using social media such as Instagram, TikTok, and WhatsApp, but they do not fully understand the risks and responsibilities associated with their use. This course discusses digital ethics, digital footprints, account security, and the dangers of hoaxes and negative content. Interactive lectures, social media simulations, group discussions, and direct practice of maintaining social media accounts are some of the techniques used. To assess the increase in participants' understanding, a simple pre-test and post-test were used during the evaluation. The results of the activity showed that participants were more aware of the importance of maintaining personal accounts and digital ethics. In addition, several students tried to become digital literacy ambassadors at school as part of the sustainability of the program. It is hoped that this activity will form positive digital habits. It will also encourage schools to incorporate digital literacy into formal learning and counseling guidance.